2019
DOI: 10.1186/s12864-019-5610-8
|View full text |Cite
|
Sign up to set email alerts
|

QTL fine-mapping of soybean (Glycine max L.) leaf type associated traits in two RILs populations

Abstract: Background The different leaf type associated traits of soybean ( Glycine max L.) including leaf area, leaf length, leaf width, leaf shape and petiole length are considered to be associated with seed yield. In order to identify quantitative trait loci (QTLs) affecting leaf type traits, two advanced recombinant inbred line (RIL, ZH, Zhonghuang 24 × Huaxia 3; GB, Guizao 1 × Brazil 13) populations were introduced to score phenotypic values in plants across nine different en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 81 publications
2
34
0
Order By: Relevance
“…Soybean ( Glycine max L.) is one of the major crops abundant in high-quality protein and oil, which also contains various nutrients such as lecithins and isoflavones [ 27 ]. Many soybean transcription factor families like WKRY [ 28 ], MYB [ 29 ], NAC [ 30 ], HD-Zip [ 31 ], ARF [ 32 ] and MADS [ 33 ] have been investigated and studied.…”
Section: Introductionmentioning
confidence: 99%
“…Soybean ( Glycine max L.) is one of the major crops abundant in high-quality protein and oil, which also contains various nutrients such as lecithins and isoflavones [ 27 ]. Many soybean transcription factor families like WKRY [ 28 ], MYB [ 29 ], NAC [ 30 ], HD-Zip [ 31 ], ARF [ 32 ] and MADS [ 33 ] have been investigated and studied.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the major QTL, q20, was co-localized to previously identified loci related to LL, LW, LA, leaf shape and seed set [14], plant height [31], and branch number [32], water use efficiency [33], and shoot phosphorus content [34], indicating the presence of important genes in this region may be involved in regulating soybean plant architecture and even yield. More importantly, we also found that q20 was colocalized with Ln, which is a key regulator of leaflet shape in soybean [19]. To further analyze the relationship between Ln gene and the leaf related traits in our study, we conducted a partial single marker analysis at the Ln locus by using investigating the association of all the molecular markers (45 SNPs) distributed in the range of within 1 Mb upstream and downstream of Ln locus with the leaf related traits, including leaf width (LW), leaf length (LL), and leaf area (LA) and chlorophyll content (CC).…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, the genetic basis of leaf-related traits and CC is still incomplete, especially the genetic relationship between these traits is surprisingly understudied. Most previous studies have focused on discrete analysis of individual traits in a single mapping population, and were limited in their ability to provide a comprehensive analysis for the genetic structure of complex quantitative traits [18,19]. Another constraint may be that only a part of the genetic structure of traits could be revealed by using the single biparental mapping populations, and prevent the excavation of specific favorable alleles [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linkage analysis between phenotypic and genotypic data was carried out by Composite Interval Mapping (CIM) method which implemented in the Windows QTLs Cartographer program version 2.5 (Wang et al 2012). CIM analysis was used to perform joint analysis of data across environments to map QTLs and estimate their genetic effects (Wang et al 2019). A series of two models were used in the analysis.…”
Section: Linkage Map Construction and Association Analysis Of Moleculmentioning
confidence: 99%